PREPARATION AND IDENTIFICATION OF SOME PVA –METAL COMPLEXES - Al-Najjar, Nada (Iraqi Journal of Science, 2024)
Some metal complexes of Poly (vinyl alcohol) (PVA) of the formula [M(PVA-oxi)2 (NO3)2] [M= Mn(II), Fe(II), Co(II) and Ni(II)] and vanadyl complex with formula [VO(PVA-oxi)2SO4] were prepared and characterized by atomic absorption, IR, UV-Vis spectroscopic techniques, molar conductance, magnetic susceptibility as well as the relIt was found that the prepared complexes were formed only with partially oxidized PVA, which has carbonyl and hydroxylic groups through PVA chains and then react with metal ion in N,N-dimethylformamide as a solvent in (1:2) molar ratio (metal : Ligand) in neutral or slightly basic solution.The results showed that the ligand (PVA-oxi) was bidentate ligand coordinated with metal ion through the oxygen atoms of carbonyl and hydroxylic groups of its chain, with an octahedral geometry around the metal ions for all the complexes.The prepared polymeric complexes are thermally stable (above 360C) which inhanced their industrial applications.